IMAGE OF THE ARMY IN THE STATE - Berdiyev Bektash (Western European Studies, 2024)
the article examines the changes that have occurred in the social institution of Uzbek society - the army - increasing prestige among the population and demand in the field of professional realization of citizens. The dynamics of changes in public consciousness regarding the army and military personnel are studied, and their causes are identified. The authors come to the conclusion that the successful targeted policy of the country's leadership was the main reason for the popularization of the army in modern conditions
Keywords: army; image; prestige; reforms